Three new species of the genus Hylaeus (Hymenoptera: Colletidae) from South Korea - Chen, Huan; Xu, Huanli (Zootaxa, 2012)
Three new species, Hylaeus (Nesoprosopis) dathei sp. nov., H. (Nesoprosopis) jirisanensis sp. nov. and H. (Nesoprosopis) koreaensis sp. nov. of the genus Hylaeus are described from South Korea. The diagnosis of each species is provided. Illustrations of male genitalia for these new species are also included.